Framework Analysis Report: Responsible Innovation and Scaling in CGIAR Instruments - Altshul, Helen J. (CGIAR System Organization, 2025)
This report reviews the CGIAR’s key instruments, including frameworks, methodologies, and tools, against the dimensions of Responsible Innovation and the principles of Responsible Scaling. It establishes a baseline for integration and highlights how existing approaches can be strengthened to make responsible innovation and scaling more intentional, inclusive, and effective within the CGIAR’s programs.